Papain-like cysteine proteases in Nicotiana benthamiana: gene family members and their potential implications in recombinant protein expression - Yang, Yalun; Deng, Zhichao; Zhang, Zhongqi; Yang, Yong; Pan, Xiaolu; Wu, Rongrong; Liu, Tao; Gao, Xiaoming; Li, Lingyan; Guo, Yongfeng (Frontiers in Plant Science, 2025)
IntroductionPapain-like cysteine proteases (PLCPs), characterized by a conserved cysteine residue at their active sites, play crucial roles in plant growth, development, and responses to biotic and abiotic stresses. While their importance in plants is well recognized, the characterization of the PLCP gene family in Nicotiana benthamiana (NbPLCP) and its involvement in biotic stress responses remains insufficiently studied. This study aims to identify NbPLCP genes in N. benthamiana and elucidate their roles in facilitating heterologous protein expression.MethodsA comprehensive bioinformatics approach was employed to identify NbPLCP genes using N. benthamiana genomic data and homology with Arabidopsis thaliana. The analysis included examination of physicochemical properties, phylogenetic relationships, gene structures, conserved motifs, expression profiles, gene duplication events, and chromosomal distribution. Virus-induced gene silencing (VIGS) was utilized to screen for genes affecting heterologous protein expression in N. benthamiana.ResultsWe identified and characterized 50 NbPLCP members. Phylogenetic analysis classified these NbPLCPs into nine subfamilies, with uneven distribution across 19 chromosomes. Comparative analysis revealed closer evolutionary relationships between N. benthamiana and Solanum lycopersicum, followed by Arabidopsis thaliana, while showing more distant relationships with Oryza sativa. Functional studies demonstrated that NbPLCPs likely participate in regulating plant growth, development, and biotic stress responses. Importantly, VIGS-mediated silencing of NbXCP1, NbXCP2, and NbXCP3 significantly enhanced the expression of heterologous GFP protein.DiscussionThis study provides comprehensive insights into the PLCP family in N. benthamiana, highlighting their functional significance and potential in heterologous protein expression. Our findings establish a foundation for understanding the evolution and function of NbPLCPs, while demonstrating their potential applications in plant biotechnology for enhancing disease resistance and improving recombinant protein production systems. These results underscore the importance of PLCPs in both plant physiology and biotechnological applications.